Incarceration and Relative Poverty in Cross-National Perspective: The Moderating Roles of Female Employment and the Welfare State - Aaron Gottlieb (Luxembourg Income Study (LIS), 2017)
A growing body of scholarship explores how incarceration contributes to inequality. The majority of this scholarship focuses on individual-level outcomes or aggregate outcomes within the United States. Despite substantial cross-national variation in incarceration rates, we know little about whether these differences contribute to cross-national variation in inequality outcomes. Using data from the period 1971-2010 from 15 advanced democracies, this study begins to fill this gap by exploring whether cross-national differences in incarceration rates help to explain cross-national differences in relative poverty rates. Although this research finds no average association, this null association obscures the important moderating role of country context. The association between incarceration and relative poverty is contingent upon a country's female employment rate and welfare state generosity.
Keywords: 330; poverty; poor; social policy; social welfare policy; welfare generosity